Inovasi Akar Rumput sebagai Proses Pemecahan Masalah : (Studi Kasus: perajin Bambu Selaawi dan perajin Sapu Ijuk Purwakarta) - Meirina Triharini; Prananda L Malasan; Raditiya A Tapoer; Muhammad Rifsan Badrus Salam; Arianti Ayu Puspita (Jurnal Sosioteknologi, 2023)
West Java is well known for its abundant natural resources and handicrafts. Because of the abundant natural resources, many handicrafts are produced by local craftsmen. One of them is bamboo handicrafts in Selaawi, which are known for their bird cages, woven bamboo baskets, and so on. Another craft in West Java that still survives and has become the hallmark of the region is the palm-fiber broom in Purwakarta. During the production process, bamboo craftsmen in Selaawi and palm-fiber broom craftsmen in Purwakarta are known to have unique production tools that are specially made for certain functions. These simple tools are developed based on the special needs of production combined with the limited availability of tools and materials. Even though it is simple in shape, this equipment is an essential production tool that plays an important part in craftsman’s production activities. Nowadays, the challenge is the lack of motivation of the younger generation who work as artisans due to economic factors and a lack of knowledge about alternative solutions to achieve affordable and simple production. Through the digitizing artifacts method, the author archived various handicraft products and their production techniques from two case study areas in craft-centers, namely Selaawi and Purwakarta. Data collection and interviews resulted in the findings that the craftsman had gone through an innovation process using a social approach.